2023
DOI: 10.3389/fpubh.2023.1191101
|View full text |Cite
|
Sign up to set email alerts
|

Sanitation-related violence against women in informal settlements in Kenya: a quantitative analysis

Samantha C. Winter,
Laura Johnson,
Millicent N. Dzombo

Abstract: IntroductionApproximately 3.6 billion people around the world do not have access to safe sanitation options. Those lacking access are not only at risk of diarrheal disease, other tropical diseases, and parasitic infections, they are at greater risk of experiencing violence, particularly women and girls. The burden of lack of access to safe sanitation is disproportionately experienced by women in informal settlements in lower- and middle-income countries, where violence rates tend to be higher and access to san… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
0
0
0
Order By: Relevance
“…Recent studies have shown that women and girls worldwide suffer safety concerns while accessing public facilities [27,28], encounter significant hurdles in achieving gender equality in the workforce [29], and experience a noticeable leadership gap [30]. The persistent gender inequities that women encounter in urban settings prompt immediate corrective action to establish more inclusive cities for women.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that women and girls worldwide suffer safety concerns while accessing public facilities [27,28], encounter significant hurdles in achieving gender equality in the workforce [29], and experience a noticeable leadership gap [30]. The persistent gender inequities that women encounter in urban settings prompt immediate corrective action to establish more inclusive cities for women.…”
Section: Introductionmentioning
confidence: 99%